Consumer acceptability and product characterization of instant peanut-based satay sauce paste - Salise, Rose Hyacinth C.
The purpose of this study was to determine the consumer acceptability and characterization of one peanut product, satay sauce. A total of 105 satay sauces in an 8-oz bottle was produced. These were used for the consumer acceptability in the laboratory and home-use test and for determining the pH and water acidity of the product. A total of fifty (50) panelists were chosen for the consumer acceptability in the laboratory scale. The satay sauce was used as a marinade for the pork barbecue. Two other existing satay sauces in market were also tested. The data were statistically analyzed using ANOVA and DMRT. For all the attributes that were tested, the formulated satay sauce has the highest scores and significantly different from the other two satay sauces. For the overall acceptability the product has a mean score of 11.42 which corresponds to like moderately. For the color acceptability, the formulated satay sauce which is medium reddish brown with 11.13 mean score was rated like moderately. The product which is slightly sweet was rated as like moderately with mean score of 10.87. For the peanut flavor acceptability, the formulated satay sauce which has slight peanut flavor was rated s like slightly with a mean score of 9.84. For the taste acceptability the product was rated as like moderately with mean score of 10.81. The product which is moderately smooth was rated as like moderately with a mean score of 10.83. Generally, the consumer s like best a satay sauce that was reddish dark brown, slightly sweet, with slight peanut flavor and a moderately mouthfeel. The taste acceptability and overall acceptability of the product is like moderately while two other existing satay sauces are rated neither like nor dislike. For the Consumer Acceptability in the Home Use Test, a total of 100 respondents from different areas in Metro Manila were given one 8-oz bottle of satay sauce and one questionnaire. Fir the overall acceptability of the product, a total of 76% like the product very much., 13% like the product moderately, 9% for a like extremely rating, 7% for a neither like nor dislike ratings and 4% for a like slightly rating. For the amount of cooking time saved when using the product, 12% said that they don't save any time at all, 49% claimed they save 11-20 minutes of cooking time, 38% 1-10 minutes and 1% for 21-20 minutes. Generally speaking, the consumer saved cooking time when using the product. For the price ranged of the product, 53% answered 21-30 pesos, 25% for 11-20 pesos range, 15% for 31-40 pesos and 7% for 1-10 pesos. The cost of the product is Php 16.62. Adding the packaging which is Php5.75, the total cost would be Php23.37. The cost of the product and the amount which the respondents were willing to pay for the product coincided with the price of the product. The pH of the product, which is 4.0, is microbiologically stable. The microorganisms that may grow at this pH are most yeast and molds. The water activity of the ingredients, which are peanut paste, catsup and worcestershire sauce.